On some problems of using digital technologies in the process of realizing individual rights and freedoms - A. A. Chomaev (Гуманитарные и юридические исследования)
Introduction. Today, it is impossible to imagine modern society without digital technologies. The introduction of such technologies has also affectedthe sphere of law, in which digitalization has become the formative legal basis of society.   The relevance of thisresearch topic is expressed in the need to identify the main problems of using digital technologies in the process of realizing individual rights and freedoms.   Materials and Methods. Based on a critical analysis of the provisions of legislation and various points of view that have developed in the general theory of law and branch sciences, the problems of using digital technologies in the process of realizing individual rights and freedoms have been identified. When writing this article, such general scientific methods as analysis, synthesis, abstraction method and modeling were also used.   Analysis. The author highlights such problems as possible discrimination based on digital data about citizens, voluntary use of digital technologies by citizens when interacting with the state. The problem of possible violations of human rights on the Internet when using digital services is revealed. It is indicated that the state must constantly develop technologies that prevent the violation of citizens’ rights in the digital space. The issue of digital competence, skills necessary for the use of electronic administrative services by both citizens themselves and civil servants, employees of organizations that use appropriate technologies in their activities is another problem that needs to be solved. There is a need for new educational technologies and specialties that allow you to form skills for the implementation of individual rights on the Internet. The problem of a theoretical nature is the lack of a unified approach to the definition of basic terms and concepts in the legislation. The opinion is expressed that the regulation of any public relations begins precisely with the development of a single conceptual framework. The author raises the issues of the lack of uniformity of norms in the regulation of procedures for the implementation of citizens’ rights and freedoms using digital technologies and the need to adopt the Digital Code of the Russian Federation.   Results. Based on the results of the conducted research, it can be concluded that there is a global need to regulate the legal realization process through the use of digital technologies.